Send me a message : - Mackey, Daphne (McGraw-Hill, 2006)
This book is useful for the intermediate learners. With the expansion of global business and the Internet, communicating clearly in written English has become essential. The step-by-step approach in the book allows learners to develop a core set of expressions and techniques for appropriate communication in a variety of written formats.